Detection of Orthopoxvirus DNA by Real-Time PCR and Identification of Variola Virus DNA by Melting Analysis - Nitsche, Andreas (American Society for Microbiology, 2004)
Although variola virus was eradicated by the World Health Organization vaccination program in the 1970s, the diagnosis of smallpox infection has attracted great interest in the context of a possible deliberate release of variola virus in bioterrorist attacks. Obviously, fast and reliable diagnostic tools are required to detect variola virus and to distinguish it from orthopoxviruses that have identical morphological characteristics, including vaccinia virus. The advent of real-time PCR for the clinical diagnosis of viral infections has facilitated the detection of minute amounts of viral nucleic acids in a fast, safe, and precise manner, including the option to quantify and to genotype the target reliably. In this study a complete set of four hybridization probe-based real-time PCR assays for the specific detection of orthopoxvirus DNA is presented. Melting analysis following PCR enables the identification of variola virus by the PCR product's characteristic melting temperature, permitting the discrimination of variola virus from other orthopoxviruses. In addition, an assay for the specific amplification of variola virus DNA is presented. All assays can be performed simultaneously in the same cycler, and results of a PCR run are obtained in less than 1 h. The application of more than one assay for the same organism significantly contributes to the diagnostic reliability, reducing the risk of false-negative results due to unknown sequence variations. In conclusion, the assays presented will improve the speed and reliability of orthopoxvirus diagnostics and variola virus identification.